Repositório de conhecimento em metodologia ativa de aprendizagem – Projeto piloto na engenharia - Junior, Lucio Garcia Veraldo; de Almeida, Benedito Manoel; Junior, Jorge Muniz; Silva, Messias Borges (My University, 2016)
Higher education institutions should be appropriate to the needs of society and especially of the labor market and the education process. Thus, employing methods where students actively learn the concepts has shown positive results in the content assimilation process. Thus, the UNISAL (Salesian University Center of São Paulo), which is the Brazilian vanguard for the use of active learning methodology, preparing teachers and promotes to use increasingly different forms of education compared to the traditional model established. Thus, different subjects in different courses have the use of innovative learning methods, but not always shared among the teachers of the institution, even outside. Thus, the creation of a digital repository with the practices applied it is necessary in order to disseminate, evaluate and criticize, for that are the proposed improvements to the established method. Therefore, the purpose of this article is through bibliographical studies, demonstrate the process of creating a repository of knowledge and apply it as a pilot project in engineering courses of the institution. To this end, a digital database will be set and can use the existing virtual platform, establishing a standard model for teachers to include information relevant to the method applied: driving process; role of the student; the evaluation process; student performance, among others. Also, it is included resources for stakeholders to interact solving doubts or proposing suggestions. With that, among the volunteer teachers will be tested and evaluated the model, according to the pedagogical information described. Once approved the tests, it is the official repository of the virtual platform.
Knowledge repository in active learning methodology - Project pilot in the engineering
Keywords: Active learning methodology; Engineering; Knowledge management; Repository; Standard 8 CDIO